PENUTUPAN LOKALISASI DOROKANDANG: ANTARA PERTIMBANGAN MORAL, SOSIAL DAN KEBUTUHAN EKONOMI - Ikayanti, Ikayanti; Lestari, Puji (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2019)
This study aims to determine the background of the closure of localization in the area of ​​Dorokandang Village, Lasem District, Rembang Regency. The dominant factors towards the closure of localization in Dorokandang Village are important to note given that so far the existence of localization in the middle of the community always reaped various pros and cons. The decision to close the localization was carried out by the Dorokandang Village government in order to deal with social problems in the form of prostitution or prostitution in the region. The research method used is a qualitative research method. The results of the study show that the background of the closure of localization in Dorokandang Village is based on several factors including moral, social and economic considerations. The hope of the Dorokandang village government with the closure of the localization was the cooperation of both the local village community, the Rembang Regency government and the Satpol PP in the supervision of the ex-localization area so that the practice of prostitution in the area would not occur in secret.